1995
DOI: 10.1099/00221287-141-1-189
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Streptococcus suis capsular type 2 haemolysin

Abstract: The production of a haemolysin by Streptococcus suis capsular type 2 was investigated. Human group 0 erythrocytes were the most susceptible, followed by horse, sheep, cow and pig red blood cells, which exhibited similar susceptibilities; rabbit erythrocytes were the least susceptible. The haemolysin was produced at the end of the exponential growth phase. The toxin described in this paper was purified by affinity chromatography using a thiopropylSepharose 6B column. It is an extracellular protein with a molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
111
1
2

Year Published

1998
1998
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(116 citation statements)
references
References 22 publications
2
111
1
2
Order By: Relevance
“…More recently, a thiol-activated haemolysin, the Suilysin, was described as a potential virulence factor of S. suis [7,12,18]. The production of this S. suis haemolysin was evidenced in strains collected from diseased pigs, but its role has not been determined [19,27].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, a thiol-activated haemolysin, the Suilysin, was described as a potential virulence factor of S. suis [7,12,18]. The production of this S. suis haemolysin was evidenced in strains collected from diseased pigs, but its role has not been determined [19,27].…”
Section: Introductionmentioning
confidence: 99%
“…nos AF106927, Z95920 and A57222) and of these, only a few are putatively involved in virulence (Smith et al, , 1993(Smith et al, , 1999Jacobs et al, 1994 ;Gottschalk et al, 1995 ;Segers et al, 1998). Previously, putative virulence factors have been identified after growth of bacteria in standard laboratory media.…”
Section: Abbreviation : Ivet In Vivo Expression Technologymentioning
confidence: 99%
“…Production of haemolysin was tested as described previously (Gottschalk et al, 1995). Production of MRP and EF was tested as described by Vecht et al (1991).…”
Section: Characterization Of Mutantsmentioning
confidence: 99%
“…Several virulence factor candidates have been proposed. These include the polysaccharide capsule, cell-wall and extracellular proteins, including muramidase-released protein (MRP), extracellular factor (EF) and adhesins, and a haemolysin (Gottschalk et al, 1995;Jacobs et al, 1994;Tikkanen et al, 1996;Vecht et al, 1991). Recent studies have shown that S. suis mutants which produce neither MRP nor EF are as virulent as the wild-type strain (Smith et al, 1996).…”
Section: Introductionmentioning
confidence: 99%